A Wide Bandgap Halide Perovskite Based Self‐Powered Blue Photodetector with 84.9% of External Quantum Efficiency (Adv. Mater. 51/2022). Issue 51 (22nd December 2022) - Yun, Yeonghun; Han, Gill Sang; Park, Gyu Na; Kim, Jihyun; Park, Jinhong; Vidyasagar, Devthade; Jung, Jina; Choi, Won Chang; Choi, Young Jin; Heo, Kwang; Kang, Joohoon; Park, Ji‐Sang; et al.
Abstract : Blue Photodetectors Vertically stacked blue/green/red photodetectors receive great attention for next‐generation image sensors, where a high‐performance blue device is the most important building block. In article 2206932, Gill Sang Han, Hyun Suk Jung, Sangwook Lee, and co‐workers demonstrate a high‐performance self‐powered blue photodetector based on wide‐bandgap halide perovskites. Outstanding external quantum efficiency (84.9%) and responsivity (0.307 A W −1 ) with improved stability is achieved by compositional engineering.